Biocentrism and its role in shaping conservation approaches in protected areas - Suryo, Kevin Ibrahim (Journal of Critical Ecology, 2025)
Background: This study explores the shift from anthropocentrism to ecocentrism in the context of protected-area prioritization in Indonesia, highlighting the influence of deep ecology and biocentrism on human-environment relationships. The primary objective of the study is to analyze the impact of deep ecology and biocentrism on conservation efforts in Indonesia, offering insights into the challenges of integrating these philosophies into environmental policymaking for long-term biodiversity conservation. Methods: This study employs a literature review methodology, analyzing existing research, philosophical frameworks, and case studies related to anthropocentrism, biocentrism, and ecocentrism in the context of environmental ethics and protected-area management. The review includes works on deep ecology, environmental ethics, and Indonesia’s specific environmental policies, drawing from both global and local perspectives to examine how these philosophies shape conservation strategies. Findings: Anthropocentrism, which views nature primarily as a resource for human use, has historically shaped environmental policies, often resulting in environmental degradation and biodiversity loss. In contrast, ecocentrism and biocentrism, which recognize the intrinsic value of all life forms, advocate for a more ethical and sustainable approach to conservation. As one of the most biodiverse countries in the world, Indonesia faces significant challenges in balancing development with biodiversity conservation, particularly in light of pressures from deforestation, agriculture, and urbanization. Conclusion: By adopting ecocentric values, Indonesia can ensure that its protected areas are managed in a way that promotes the sustainability of both human and natural systems. Novelty/Originality of This Study: This study introduces a novel approach by integrating deep ecology and biocentrism into protected-area prioritization in Indonesia. It offers fresh insights into how these ethical frameworks can reshape conservation policies for long-term biodiversity sustainability.